The impact of IT resources and strategic alignment on organizational performance: The moderating role of environmental uncertainty - Masume Pashutan; Neda Abdolvand; Saeedeh Rajaee Harandi (Digital Business, 2022)
Today, organizations make significant investments in information technology (IT) as a strategic resource to achieve their goals. If these investments are managed properly, they can create value for the organization. However, companies face problems in evaluating IT investment plans to gain value from them and improve organizational performance, which can be attributed to different reasons such as environmental uncertainty. Therefore, this study used a resource-based view and evaluated the impact of IT investment, IT management as two important IT resources, and strategic alignment on organizational performance by considering the moderating role of environmental uncertainty as one of the most important challenges of companies in IT usage. The quantitative approach was used and the required data was gathered using two questionnaires (one for IT managers and one for executives). The questionnaires were collected randomly from 70 IT managers, and 70 CIOs, and CEOs of small and medium-sized IT organizations (SMEs). Then data was analyzed using Structural Equation Modeling through using PLS software. Based on the results, strategic alignment and IT management are effective on organizational performance. Besides, environmental uncertainty moderated these relationships. The results of the study will help managers to nurture IT resources in their company to develop their strategies based on their perceived level of environmental uncertainty.
Keywords: 650; IT investment; IT management; Strategic alignment; Environmental uncertainty; Organizational performance